STUDI PENGARUH PENGGUNAAN ASAM SULFAT PADA PEMBUATAN REDUCED CHROME TANNING AGENT SERTA KARAKTERISASINYA - Prasetyo Hermawan; Swatika Juhana (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2020)
The purpose of this research was to study the effect of the weight of using H2SO4 in the manufacture of reduced chrome tanning agent. The raw materials used are salt Na2Cr2O7, molasses and H2SO4 and control is needed when adding molasses and H2SO4 because the reaction is exothermic. Reduced chromium liquid is made by varying the weight of using H2SO4; 15.5gr, 16.6gr, 18.2gr, 20gr and 26.6gr. Furthermore, the character of the reduced chromium material is tested, including using the standard SNI: 06-4993-1999 testing related to the basicity value test. The added weight of using H2SO4 at all levels of variation when producing reduced chrome yields a dark green color of the reduced chromium liquid product. In addition to the weight of using H2SO4 from 15.5 gr to 26.6 gr, there was a decrease in the basicity value from 65.91% to 0%, a decrease in the pH value from 2.83 to 1.01 and also a decrease in water content from 45.28% to 36.92%. In addition, the weight of H2SO4 was used as much as 18.2 gr, 20 gr and 26,6 gr, then by using the spectophotometric method, the average Cr (IV) concentration was obtained at 44.4 mg/L and Cr (III) was 331.9 mg/L. The weight of H2SO4 used from 18.2gr to 26.6gr decreased the yield from 91.9% to 84.01%.